2017
DOI: 10.1111/pce.12968
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of glyoxalase pathway confers tolerance to multiple stresses in rice

Abstract: Crop plants face a multitude of diverse abiotic and biotic stresses in the farmers' fields. Although there now exists a considerable knowledge of the underlying mechanisms of response to individual stresses, the crosstalk between response pathways to various abiotic and biotic stresses remains enigmatic. Here, we investigated if the cytotoxic metabolite methylglyoxal (MG), excess of which is generated as a common consequence of many abiotic and biotic stresses, may serve as a key molecule linking responses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(79 citation statements)
references
References 52 publications
5
74
0
Order By: Relevance
“…Therefore, it would not be inappropriate to term MG and glyoxalases as possible biomarkers of plant stress tolerance [15]. To this end, over-expression of glyoxalase pathway genes has been carried out in various plant species wherein through improved MG detoxification as a result of increased activity of glyoxalase pathway enzymes, MG levels could be restricted from rising under stress, thereby imparting enhanced stress tolerance to plants [33,[35][36][37][38]. Previous genome-wide studies carried out in Arabidopsis, Oryza sativa [18], Glycine max [19], Medicago truncatula [20] and Brassica rapa [21] have identified the presence of glyoxalase pathway genes as multiple members in these plant species and shown them to be differentially regulated in response to various abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it would not be inappropriate to term MG and glyoxalases as possible biomarkers of plant stress tolerance [15]. To this end, over-expression of glyoxalase pathway genes has been carried out in various plant species wherein through improved MG detoxification as a result of increased activity of glyoxalase pathway enzymes, MG levels could be restricted from rising under stress, thereby imparting enhanced stress tolerance to plants [33,[35][36][37][38]. Previous genome-wide studies carried out in Arabidopsis, Oryza sativa [18], Glycine max [19], Medicago truncatula [20] and Brassica rapa [21] have identified the presence of glyoxalase pathway genes as multiple members in these plant species and shown them to be differentially regulated in response to various abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of GSH in KN treated plants may have contributed significantly to the maintenance of the glyoxylase system for elimination of methylglyoxal, which may decline the chances of any serious genotoxic effect [72]. Glyoxylase I and II form the key enzymatic components of the glyoxylase system, and KN-induced up-regulation in their activities, accompanied by the increased GSH, may have led to exploit the beneficial effects of methylglyoxal like crosstalk with important signaling molecules like Ca, ROS and ABA [73].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in salt stressed rice, Rahman et al [12] have also demonstrated up-regulation of the glyoxylase system. Enhanced activity of the glyoxylase system due to exogenous application of KN may have protected the electron transport system by preventing damage to chloroplast and mitochondrial ultrastructures [72]. …”
Section: Discussionmentioning
confidence: 99%
“…The role of the glyoxalase system in resistance to multiple biotic and abiotic stresses has been well characterised in some studies. Recently, it has been reported that the glyoxalase pathway of rice not only increases tolerance to salinity, drought and extreme temperatures but also reduces damage from sheath blight fungus (Rhizoctonia solani) [69]. Moreover, some glyoxalase members of soybean such as GmGLYI-6/9/20 and GmGLYII-6/10 show special expression patterns in response to various pathogenic infection [9].…”
Section: Different Expression Patterns Of Glyoxalase Genes In Responsmentioning
confidence: 99%